![image](https://tex.z-dn.net/?f=y%3D+%5Cfrac%7B+%5Csqrt%7B6x%2B+x%5E%7B2%7D+%7D%2B3+%7D%7B+%5Csqrt%7Bx-3%7D++%7D++%5C%5C++%5Cleft+%5C%7B+%7B%7B6x%2B+x%5E%7B2%7D++%5Cgeq+0%7D+%5Catop+%7Bx-3%3E0%7D%7D+%5Cright.+%3D%3E%5Cleft+%5C%7B+%7B%7Bx%286%2Bx%29++%5Cgeq+0%7D+%5Catop+%7Bx%3E3%7D%7D+%5Cright.+%5C%5C+x%286%2Bx%29+%5Cgeq+0+%5C%5C+x_1%3D0%3B+x_2%3D-6+%5C%5C++%5C%5C++%5Cleft+%5C%7B+%7B%7Bx+%5Cin+%28-+%5Cinfty%3B-6%5D+%5Ccup+%5B0%3B%2B%5Cinfty%29%7D+%5Catop+%7Bx%3E3%7D%7D+%5Cright.+%3D%3E+x+%5Cin+%283%3B%2B%5Cinfty%29)
0}} \right. =>\left \{ {{x(6+x) \geq 0} \atop {x>3}} \right. \\ x(6+x) \geq 0 \\ x_1=0; x_2=-6 \\ \\ \left \{ {{x \in (- \infty;-6] \cup [0;+\infty)} \atop {x>3}} \right. => x \in (3;+\infty)" alt="y= \frac{ \sqrt{6x+ x^{2} }+3 }{ \sqrt{x-3} } \\ \left \{ {{6x+ x^{2} \geq 0} \atop {x-3>0}} \right. =>\left \{ {{x(6+x) \geq 0} \atop {x>3}} \right. \\ x(6+x) \geq 0 \\ x_1=0; x_2=-6 \\ \\ \left \{ {{x \in (- \infty;-6] \cup [0;+\infty)} \atop {x>3}} \right. => x \in (3;+\infty)" align="absmiddle" class="latex-formula">